Rekomendasi Pengembangan Optimalisasi Akuntansi dan Pengelolaan Keuangan untuk Meningkatkan Efisiensi Produksi Olahan Lele di CV. Chosyle - Rahmansyah, Ahmad Iskandar; Masluha, Siti; Hendra, Joni; Bahri, Mohammad Saiful; Ghalda, Hisbinnisa Hasna Aulia; Pramana, Zalfa' Nur Auliya Putri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2023)
This community service aims to optimize the accounting and financial management system at CV Chosyle, a processed catfish production company, in order to enhance efficiency in production and operational processes. In the context of intense business competition, effective financial management becomes pivotal in achieving sustainable growth. The methodology of this community service involves in-depth analysis of the current accounting structure and cash flow within CV Chosyle, followed by the development of recommendations for improvement. The implementation of an appropriate accounting system will aid in monitoring and managing expenses and revenues more accurately. Meticulous financial management will mitigate the risk of resource wastage and ensure efficient allocation of funds for investment and business development. The anticipated outcomes include heightened financial control, improved decision-making, and optimized resource utilization. Consequently, CV Chosyle is poised to experience elevated productivity, enhanced production quality, and heightened competitiveness in the market.